Enasidenib in mutant IDH2 relapsed or refractory acute myeloid leukemia - Stein, Eytan M.; DiNardo, Courtney D.; Pollyea, Daniel A.; Fathi, Amir T.; Roboz, Gail J.; Altman, Jessica K.; Stone, Richard M.; DeAngelo, Daniel J.; Levine, Ross L.; Flinn, Ian W.; Kantarjian, Hagop M.; Collins, Robert; et al. (Blood, 2017)
Recurrent mutations in isocitrate dehydrogenase 2 (IDH2) occur in ∼12% of patients with acute myeloid leukemia (AML). Mutated IDH2 proteins neomorphically synthesize 2-hydroxyglutarate resulting in DNA and histone hypermethylation, which leads to blocked cellular differentiation. Enasidenib (AG-221/CC-90007) is a first-in-class, oral, selective inhibitor of mutant-IDH2 enzymes. This first-in-human phase 1/2 study assessed the maximum tolerated dose (MTD), pharmacokinetic and pharmacodynamic profiles, safety, and clinical activity of enasidenib in patients with mutant-IDH2 advanced myeloid malignancies. We assessed safety outcomes for all patients and clinical efficacy in the largest patient subgroup, those with relapsed or refractory AML, from the phase 1 dose-escalation and expansion phases of the study. In the dose-escalation phase, an MTD was not reached at doses ranging from 50 to 650 mg per day. Enasidenib 100 mg once daily was selected for the expansion phase on the basis of pharmacokinetic and pharmacodynamic profiles and demonstrated efficacy. Grade 3 to 4 enasidenib-related adverse events included indirect hyperbilirubinemia (12%) and IDH-inhibitor–associated differentiation syndrome (7%). Among patients with relapsed or refractory AML, overall response rate was 40.3%, with a median response duration of 5.8 months. Responses were associated with cellular differentiation and maturation, typically without evidence of aplasia. Median overall survival among relapsed/refractory patients was 9.3 months, and for the 34 patients (19.3%) who attained complete remission, overall survival was 19.7 months. Continuous daily enasidenib treatment was generally well tolerated and induced hematologic responses in patients for whom prior AML therapy had failed. Inducing differentiation of myeloblasts, not cytotoxicity, seems to drive the clinical efficacy of enasidenib. This trial was registered at www.clinicaltrials.gov as #NCT01915498. •Enasidenib, a selective inhibitor of mutant IDH2 enzymes, was safe and well tolerated in patients with IDH2-mutated myeloid malignancies.•Enasidenib induced hematologic responses in patients with relapsed/refractory AML in this dose-escalation and expansion study.